Improving national and international surveillance of movement behaviours in childhood and adolescence: an international modified delphi study - Reilly, J. J; Andrew, R.; Abdeta, C.; Azevedo, L. B.; Aguilar Farias, N.; Barak, S.; Bardid, F.; Bizzozero-Peroni, B.; Brazo-Sayavera, J.; Cagas, J. Y.; Chelly, M.-S.; Christiansen, L. B.; et al. (Sports Medicine, 2025)
Background: The actions required to achieve higher-quality and harmonised global surveillance of child and adolescent movement behaviours (physical activity, sedentary behaviour including screen time, sleep) are unclear. Objective: To identify how to improve surveillance of movement behaviours, from the perspective of experts. Methods: This Delphi Study involved 62 experts from the SUNRISE International Study of Movement Behaviours in the Early Years and Active Healthy Kids Global Alliance (AHKGA). Two survey rounds were used, with items categorised under: (1) funding, (2) capacity building, (3) methods, and (4) other issues (e.g., policymaker awareness of relevant WHO Guidelines and Strategies). Expert participants ranked 40 items on a five-point Likert scale from `extremely` to `not at all` important. Consensus was defined as > 70% rating of `extremely` or `very` important. Results: We received 62 responses to round 1 of the survey and 59 to round 2. There was consensus for most items. The two highest rated round 2 items in each category were the following; for funding (1) it was greater funding for surveillance and public funding of surveillance; for capacity building (2) it was increased human capacity for surveillance (e.g. knowledge, skills) and regional or global partnerships to support national surveillance; for methods (3) it was standard protocols for surveillance measures and improved measurement method for screen time; and for other issues (4) it was greater awareness of physical activity guidelines and strategies from WHO and greater awareness of the importance of surveillance for NCD prevention. We generally found no significant differences in priorities between low-middle-income (n = 29) and high-income countries (n = 30) or between SUNRISE (n = 20), AHKGA (n = 26) or both (n = 13) initiatives. There was a lack of agreement on using private funding for surveillance or surveillance research. Conclusions: This study provides a prioritised and international consensus list of actions required to improve surveillance of movement behaviours in children and adolescents globally.